2019
DOI: 10.1016/j.molcel.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 (B7-H1) Competes with the RNA Exosome to Regulate the DNA Damage Response and Can Be Targeted to Sensitize to Radiation or Chemotherapy

Abstract: Highlights d Intracellular PD-L1 binds RNA and regulates the RNA stability of DNA damage genes d PD-L1 competes with the RNA exosome to regulate RNA stability globally d PD-L1 is important for proper DNA damage response and repair d The PD-L1 antibody H1A sensitizes tumors to DNA-damaging therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
160
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 39 publications
6
160
0
Order By: Relevance
“…A PD-L1 antibody, H1A, was developed to destabilize PD-L1 by disrupting the PD-L1 stabilizer CMTM6. This disruption resulted in PD-L1 degradation through the lysosome and increased sensitivity to radiotherapy and cisplatin (4). These studies indicate that targeting intracellular PDL1 may enhance the efficacy of chemotherapy or radiotherapy by overcoming PDL1 mediated drug resistance (Figure 2).…”
Section: Crosstalk Between the Dna Damage Response And Immune Checkpomentioning
confidence: 92%
See 3 more Smart Citations
“…A PD-L1 antibody, H1A, was developed to destabilize PD-L1 by disrupting the PD-L1 stabilizer CMTM6. This disruption resulted in PD-L1 degradation through the lysosome and increased sensitivity to radiotherapy and cisplatin (4). These studies indicate that targeting intracellular PDL1 may enhance the efficacy of chemotherapy or radiotherapy by overcoming PDL1 mediated drug resistance (Figure 2).…”
Section: Crosstalk Between the Dna Damage Response And Immune Checkpomentioning
confidence: 92%
“…PD-L1 has been well-known as immune checkpoint inhibition to the activation of T cells by interacting with PD1. PD-L1 was recently found as a novel RNA binding protein to increase drug resistance in cancer cells by increasing mRNA stability of various mRNAs encoding for proteins involved in DDR and repair (4). Luo lab reported that PD-L1 acts as an RNA binding protein to protect target RNAs from degradation by interacting with EXOSC10 and EXOSC4, which are key components of the RNA exosome (4).…”
Section: Crosstalk Between the Dna Damage Response And Immune Checkpomentioning
confidence: 99%
See 2 more Smart Citations
“…As a regulatory molecule of PD-L1, CMTM6 enhances the cell surface expression of PD-L1. The upstream and downstream relationship between CMTM6 and PD-L1 may participate in the formation of tumor related pathways [14]. Few studies have examined CMTM6 and PD-L1 in GC.…”
mentioning
confidence: 99%